A Case Report : Bronchopleural Fistula Dextra with Pyopneumothorax Dextra as Complication of Lung Tuberculosis - Wahyudy Prasetyo, Kevin; Jani, Jane R Sugiri; Dini, Rachma Erawati; Wardhana, Kurnia (Malang Respiratory Journal, 2023)
Background: Bronchopleural fistula is a rare case that might be caused by trauma, post lung resection surgery, and non traumatic cause such as lung Tuberculosis infection. Bronchopleural fistula is a serious complication of lung TB which almostly related to pleural cavity infection. This fistula condition may be accompanied with empyema that can cause secondary spontaneous pneumothorax. The diagnosis of fistula is established by combination of clinical symptoms regarding lung TB infection, radiology, laboratory, microbiology, dan histopathologi examinations. Management of bronchopleural fistula includes chest tube insertion to treat pyopneumothorax problem, fistula repair surgery, and underlying disease and its comorbid. Case: We report one case located at Dr. Saiful Anwar hospital, a 36 year old woman with symptoms of dyspneu and chronic cough with purulent sputum. Based on the clinical data, laboratory results, radiological imaging, sputum examination, and plerual fluid analysis and cytology, diagnosis of bronchopleural fistula together with pyopneumothorax as complication of lung TB was made. Management of this patient comprises of chest tube insertion, fistula repair surgery, antibiotic, and OAT. Conclusion: Bronchopleural fistula is a rare case found. Proper surgical management and treating underlying disease such as lung TB might improve clinical outcome and reduce mortality rate. Keywords: Bronchopleural fistula, Pyopneumothorax, Lung TB